Analysis of anti-poverty policy fragmentation from regional planning perspective - Wei, Ya-Ping; Luo, Wen-Liang; Jiang, Chi (Zhejiang da xue xue bao. Journal of Zhejiang University. Sciences edition. Li xue ban, 2013)
Based on the concept of "fragmentation", the fragmentation of China's poverty-counties policy was analyzed. This issue covers three main aspects, including compartmentalization of the subject of liabilities, isolation of specific policies, and lack of policy evaluation system. The fragmentation of poverty-counties policy reflects a number of system issues in the overall socio-economic development. The paper considered that it is necessary to build a comprehensive anti-poverty policy system, which will help to determine the direction of policy implementation and finally contribute to healthy urbanization. In the end, it developed policy suggestions to establish a comprehensive policy integration mechanism.